Answer:
- f(1) = -24; f(n) = 4·f(n-1)
- f(1) = 13; f(n) = f(n-1) + 26
- f(1) = 28; f(n) = -4·f(n-1)
Step-by-step explanation:
Identify the first term of the sequence. First terms are -24, 13, 28. Find the matching f(1). There are two choices for each first term.
Then determine the relation of each term to the previous term. In two of the sequences, a factor of 4 is involved. For the sequence starting with -24, the adjacent terms have the same sign, so the factor is +4. For the sequence starting with 28, adjacent terms have alternating signs, so the factor is -4.
For the sequence starting with 13, the second term is 3 times the first, but it is also 26 added to the first. You have to look at the next term to see if the sequence is geometric with a ratio of 3, or arithmetic with a difference of 26. The latter is the case, so the recursive definition will involve addition, not multiplication.
The recursively defined functions are shown above in the order of the given sequences.
Answer:
64 bats can eat 320 grams of insects in 1 night.
Step-by-step explanation:
Answer:
1042
Step-by-step explanation:
-38,-8,22,52
The common difference is 52 - 22 = 30
a_1 = -38
a_2 = -38 + 30
a_3 = -38 + 2 * 30
a_4 = -38 + 3 * 30 (notice that the common difference is multiplied by 1 less than the term number)
a_n = -38 + (n - 1)30 (since the term number is n, we multiply the common difference by n - 1)
a_n = -38 + 30(n - 1)
a_37 = -38 + 30(37 - 1)
a_37 = 1042
Answer:
a.7(6xy-2z)
=7*6xy-7*2z
=42xy-14z
b.5(2w+3)-6(w+2)
=5*2w+5*3-6*w-6*2
=10w+15-6w-12
=4w+3
c.2f(2f+g-3)
=2f*2f+2f*g-2f*3
=4f^2+2fg-6f
Step-by-step explanation:
The answer is x1= 0, x2= 6